Isolation, screening and characterization of bacteria associated with cocoa tree roots for different plant growth promotion (PGP) activities - Madian, Nurfadzilah; Mohd Saud, Halimi; Ahmad, Fisal; Tan, Geok Hun (Malaysian Society for Microbiology, 2021)
Aims: Plant growth promoting rhizobacteria (PGPR) is a group of bacteria that colonise plant roots and enhance plant growth by a diverse range of mechanisms. This study aims to determine the capabilities of PGPR isolated from cocoa tree roots and their efficiency in enhancing plant growth under greenhouse conditions. Methodology and results: Eight samples of healthy cocoa tree roots were collected from different locations in Malaysia. Isolated bacteria were screened based on nitrogen fixation, phosphate and potassium solubilization, and catalase activity. The efficiency of purified PGPR was evaluated from pot experiments of cocoa seedlings under greenhouse conditions. Out of 122 isolates, 18 isolates showed several traits of nitrogen fixation, phosphorus and potassium solubilization and were further screened for other plant growth promoting (PGP) traits like catalase and production of indole acetic acid (IAA). Out of all the PGP trait tests, seven isolates showed the most prominent results for in vitro tests and were further tested in vivo for growth promotion of cocoa seedlings under greenhouse conditions. In the presence of bacterial isolates with 2.5 g of inorganic fertilizer, Leclercia adecarboxylata resulted in increases in plant height, leaf number, root length, stem fresh weight and total fresh and dry weight of cocoa seedlings by 15.68%, 17.14%, 9.48%, 5.67%, 11.84% and 25.12%, respectively. Conclusion, significance and impact of study: Based on the result, L. adecarboxylata incorporated with selected carrier material improve cocoa seedling growth and biomass. This formulation also reduces the production cost of inorganic fertilizer and increase the application and development of biofertilizer.